2020
DOI: 10.1038/s41419-020-2331-5
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear gene rpl18 regulates erythroid maturation via JAK2-STAT3 signaling in zebrafish model of Diamond–Blackfan anemia

Abstract: Diamond-Blackfan anemia (DBA) is a rare, inherited bone marrow failure syndrome, characterized by red blood cell aplasia, developmental abnormalities, and enhanced risk of malignancy. However, the underlying pathogenesis of DBA is yet to be understood. Recently, mutations in the gene encoding ribosomal protein (RP) L18 were identified in DBA patients. RPL18 is a crucial component of the ribosomal large subunit but its role in hematopoiesis remains unknown. To genetically model the ribosomal defect identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…1f, g ). Our previous study demonstrated that loss of ribosomal protein (RP) genes in zebrafish often results in a small head, small eyes, and enlarged hindbrain ventricles 20 , 21 . The same phenotype was observed in rpl17 -NGA PAM knockout F0 embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1f, g ). Our previous study demonstrated that loss of ribosomal protein (RP) genes in zebrafish often results in a small head, small eyes, and enlarged hindbrain ventricles 20 , 21 . The same phenotype was observed in rpl17 -NGA PAM knockout F0 embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rpl18 is an important component of the large subunit of ribosome and plays an important role in ribosome assembly. C Chen [ 39 ] reported that Rpl18 regulates erythroid maturation via JAK2/STAT3 signaling. Loh JT [ 40 ] demonstrated that suppressing JAK2/STAT3 signaling in neutrophils was important for intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature of the genetic defects, this proinflammatory innate immune response could indeed be attributed to endogenous factors, such as aberrant RNA components resulting from disrupted ribosome assembly. Whether inflammatory signaling is a side effect or an integral part of the pathogenic mechanism in DBA models has been addressed in a more recent rpl18 zebrafish mutant study ( Chen et al, 2020 ). Like multiple other ribosomopathy zebrafish models, rpl18 mutants activate p53 and JAK-STAT pathways.…”
Section: Ribosomopathies Cytopenias and Inflammatory Signalingmentioning
confidence: 99%